Plant circadian rhythms regulate the effectiveness of a glyphosate-based herbicide - Fiona E. Belbin (Nature Portfolio, 2019)
Glyphosate is the world’s most widely-used herbicide. Here, Belbin et al. show that plant responses to glyphosate, and therefore herbicide activity, depend on plant circadian rhythms suggesting that considering the time-of-day of application could lead to more efficient agrochemical use.